The Role of Multimodalities Approach in Diagnosing Disorders of Sex Development (DSD): Brief Review - Ziske Maritska; Masagus Irsan Saleh Hasani; Fachmi Idris; Zen Hafy; Didit Pramudhito; Kemas Yusuf Effendi (Sriwijaya Journal of Medicine, 2024)
Disorders of Sex Development (DSD) encompass rare congenital conditions involving atypical development of chromosomes, gonads, or sex anatomy. The 2006 global consensus led to a shift in the approach to handling DSD cases, emphasizing integrated treatment involving various scientific disciplines. DSD diagnosis involves a structured and multimodality approach, including history, pedigree analysis, physical examination, imaging, hormone and chromosome analysis, and genetic testing. An in-depth anamnesis and detailed pedigree analysis help trace family history and inheritance patterns of Mendelian traits in DSD cases. Thorough physical examination, including general and specific assessments, helps screen for abnormalities in sexual development. Karyotyping, hormone level investigation, and imaging examinations are crucial for supporting the diagnosis of DSD. However, genetic or molecular examination remains the modality for definitively confirming the genetic disorder underlying DSD, subsequently leading to a better understanding and management of the condition. Considering the limited resources available in the field in efforts to establish a molecular diagnosis of DSD, it is recommended to explore the role of anamnesis, pedigree analysis, physical examination, imaging examination, hormonal laboratory examination, and chromosome analysis in efforts to approach the diagnosis of DSD.